Rancang Bangun Aplikasi Augmented Reality Berbasis Mobile untuk Pembelajaran Flora dan Fauna - Paliling, Alders; Mardiawati, Mardiawati; Agies Al Kasyaf, Muhammad (Jurnal Manajemen Informatika JAMIKA, 2025)
The purpose of this research is to create an Android-based Augmented Reality (AR) application that can be used as an interactive learning media that will teach endemic flora and fauna of Indonesia at the junior high school level. This application is built with Unity and Vuforia, utilizing twenty 3D models that can be accessed through a marker-based tracker, and equipped with quiz and audio story features. Development involved compatibility testing on various Android devices with 13 students and instructors at SMP Negeri 5 Tanggetada. The results showed optimal functionality based on black box testing and a user satisfaction level of 91.53% from UAT. This application increases student engagement through interactive 3D visualizations that are tailored to user feedback.